Unveiling the hidden culprit: ossification posterior longitudinal ligament (OPLL) with central cord syndrome in a post - traumatic diparesis patient - Nordin, Muhammad Shukri; Abu Hasan, Muhammad Abdus-Syakur (College of Emergency Physician Academy of Medicine Malaysia (CEP AMM), 2025)
Introduction: Ossification of the posterior longitudinal ligament (OPLL) is uncommon condition characterized by abnormal calcification of the ligament along the spinal column, most commonly in the cervical region. While it typically affects older adults, its presence in younger individuals is unusual and can increase the risk of spinal cord injury (SCI) even with minor trauma. This case report highlights a patient with traumatic central cord syndrome (CCS) in the context of OPLL, emphasizing the importance of early identification and management.